Governing Food Security in The Low-Carbon Transition: A SEM Analysis of Sustainable Industrialization, Sustainable Remediation, and Circular Supply Chain Governance - Arie Wahyu Prananta; I Wayan Suyadnya; Indra Jaya Kusumawardana; Zainal Abidin (Economics and Business Journal (ECBIS), 2026)
Food security in the low-carbon transition is increasingly shaped by industrial decarbonization, environmental restoration, and circular supply-chain coordination, yet these domains are often modeled as separate sustainability agendas. This study addresses the gap by developing a governance-centered structural equation model that links sustainable industrialization, sustainable remediation, circular supply chain governance, and food-security outcomes. Using the available 455-response dataset, the empirical test operationalizes industrialization intensity (IND) as a proxy for sustainable industrialization, digital-institutional capability (DIC) as a proxy for circular governance capability, and social-economic resilience (SER) as a proxy for food-system security. Confirmatory factor analysis supports the measurement model: standardized loadings range from .778 to .849 for IND, .804 to .835 for DIC, and .800 to .843 for SER; CR values range from .901 to .914; AVE ranges from .646 to .681; and model fit is acceptable (chi-square/df = 2.108, CFI = .961, TLI = .951, RMSEA = .049, SRMR = .038). The SEM results show that IND significantly predicts DIC (beta = .537, p < .001), DIC predicts SER (beta = .424, p < .001), and IND retains a direct effect on SER (beta = .337, p < .001). The indirect effect is significant (beta = .228, 95% CI [.178, .282]). The article contributes a cautious, data-grounded framework for analyzing food security as a governance-mediated outcome of low-carbon industrial transition.